Evaluation of Serpentine-Type Heat Exchanger Application on Water Heater with Passages Number Variation - I Gede Arya Dimas Wisnu Murti Surawardana; Made Sucipta; Hendra Wijaksana (HM Publisher, 2023)
For some people, using warm water for bathing needs is a tertiary need because getting warm water requires additional costs. Generally, people/industry use water heaters that are sold in the market. These water heaters generally use electricity, solar power, or natural gas. This study aimed to evaluate the use of heat recovery systems as water heaters with variations in the number of passages. This research is an experimental study on a serpentine-type heat exchanger. Tests were carried out on standard split air conditioners and split air conditioners integrated with heat exchangers. The independent variables in this study were variations of the heat exchanger type serpentine with a length of 4 m, with each heat exchanger having a height of 20, 25, and 30 cm, with variations of 10, 12, and 14 passages and variations of evaporator output air settings 16ºC, 20ºC and 24ºC. The use of the evaporator outlet air temperature setting produces a different refrigeration effect value. The lower the evaporator output air temperature setting, the lower the resulting refrigeration effect value. The air temperature leaving the evaporator is 24ºC which results in a higher refrigeration effect value. This study showed the best heater performance at the evaporator air setting of 16ºC with a variation of 10 passages. In conclusion, the addition of a heat recovery system with serpentine-type heat exchanger variations 10 passages, 12 passages, 14 passages, and 24°C temperature loading variations, 20°C and 16°C on the evaporator burst will have an impact on decreasing the coefficient of performance on the split air conditioner system.